Assessment Practices in Online Mathematics Learning: Insights from Nepali Universities - Adhikari, Krishna Prasad; Sharma, Lekhnath; Joshi, Dirgha Raj (Interdisciplinary Research in Education, 2025)
After the outbreak of COVID-19, Nepal’s universities have been adopting online or blended learning systems; however, the quality and credibility of online assessment practices within this emerging system remain unexplored. This study explored how teachers and students experience online assessment design, implementation, and integrity in mathematics. Data was collected through semi-structured interviews and LMS observations from six students and six teachers from three universities using an interpretive research design and were analyzed thematically. The findings show that assessment mainly focuses on assessment of learning rather than as and for learning, a lack of a systematic feedback mechanism, and an authorship checking system. Plagiarism and cheating are major challenges to maintaining the academic integrity of the assessment process. Despite these challenges, some instructors demonstrated effective use of rubrics, automated tools, and authentic assessment design, indicating emerging but uneven progress toward transparent and technology-enhanced assessment.